Cultiv8Me.PH – Business and Employment-Oriented Online Service System - Boongaling, Krystaleen G.; Del Rosario, John Vincent M.; Gampong, Hannah Isabel F.; Mendoza, Christian Paul P. (International Journal of Computing Sciences Research, 2024)
Purpose – The project aims to support interns and alumni in their career growth by offering them opportunities to showcase their skills and secure suitable job positions through an application. This app streamlines the tedious process of finding job openings in companies. Method – The researchers adopted the Scrum development model for its adaptability, teamwork, and continuous development aspects. They assessed system quality using a FURPS evaluation with a Likert scale questionnaire and calculated mean scores using the weighted mean statistical approach. Results – The web application scored highest in supportability and usability, while the mobile app excelled in supportability, functionality, and performance. Both applications received positive feedback for their user-friendly interfaces and effective functionalities. Conclusion – The study successfully developed a business and employment-oriented system for the IALAP office, earning high ratings in functionality, usability, reliability, performance, and supportability. Respondents showed strong agreement and satisfaction with both the web and mobile applications. Recommendations – The study suggests implementing a web API-based notification system, enabling real-time mobile data checking, improving security algorithms, integrating special case support for interns, and utilizing machine learning and AI for Career Path Planning. Research Implications – This study's results hold significant value for the client, providing valuable data on alumni and facilitating career planning for students and interns seeking job opportunities aligned with their skills and interests.